Implementation of MABAC Method and Entropy Weighting in Determining the Best E-Commerce Platform for Online Business - Wang, Junhai; Darwis, Dedi; Setiawansyah, Setiawansyah; Rahmanto, Yuri (JiTEKH, 2024)
The main problem in choosing an e-commerce platform for an online business is finding the one that best suits the specific needs of the business. Each platform has its advantages and disadvantages, such as ease of use, cost, features offered, as well as support for inventory management, shipping, and payments. Other challenges include ensuring that the platform can support future business growth, offer good scalability, and provide flexibility in terms of customization and integration with digital marketing tools. In addition, data security and a good user experience are also important considerations for long-term success. The purpose of this study is to implement the MABAC method and Entropy weighting in determining the best e-commerce platform for online businesses, so that this research can provide clear and data-driven recommendations to stakeholders regarding the most effective e-commerce platform. The application of the MABAC method combined with Entropy weighting in determining the best e-commerce platform for online business people offers a comprehensive and objective approach in decision-making. This combination not only improves decision-making accuracy, but also ensures that the most important criteria are weighted accordingly, resulting in more reliable results in choosing the best platform for business needs. The final result of the MABAC Platform A score is the first choice, considering the highest score of 0.82, which indicates its optimal performance in meeting the criteria that have been set. In addition, Platforms B and C, with scores of 0.78 and 0.75, respectively.